Epstein‐Barr virus viral load and serology in childhood non‐Hodgkin's lymphoma and chronic inflammatory conditions in Uganda: Implications for disease risk and characteristics. Issue 10 (2nd June 2014) - Orem, Jackson; Sandin, Sven; Mbidde, Edward; Mangen, Fred Wabwire; Middeldorp, Jaap; Weiderpass, Elisabete
<x xml:space="preserve">Abstract</x> Epstein‐Barr virus (EBV) has been linked to malignancies and chronic inflammatory conditions. In this study, EBV detection was compared in children with non‐Hodgkin's lymphoma and children with chronic inflammatory conditions, using samples and data from a case‐control study carried out at the Mulago National Referral Hospital between 2004 and 2008. EBV viral load was measured in saliva, whole blood and white blood cells by real‐time PCR. Serological values for IgG‐VCA, EBNA1, and EAd‐IgG were compared in non‐Hodgkin's lymphoma and chronic inflammatory conditions; and in Burkitt's lymphoma and other subtypes of non‐Hodgkin's lymphoma. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were calculated. Of the 127 children included (87 males and 40 females; median age 7 years, range 2–17), 96 had non‐Hodgkin's lymphoma (46 Burkitt's lymphoma and 50 other non‐Hodgkin's lymphoma), 31 had chronic inflammatory conditions, and only 10% were HIV‐positive. The most common clinical presentations for all disease categories considered were fever, night sweats, and weight loss. EBV viral load in whole blood was elevated in Burkitt's lymphoma compared to other non‐Hodgkin's lymphoma (OR 6.67, 95% CI 1.32, 33.69; P‐value = 0.04), but EBV viral loads in saliva and white blood cells were not different in any of the disease categories considered. A significant difference in EAd‐IgG was observed when non‐Hodgkin's lymphoma was compared with chronic inflammatory conditions (OR 0.19, 95% CI 0.07, 0.51; P‐value = 0.001). When compared to chronic inflammatory conditions, EBV viral load was elevated in Burkitt's lymphoma, and EA IgG was higher in non‐Hodgkin's lymphoma. This study supports an association between virological and serological markers of EBV and childhood non‐Hodgkin's lymphoma, irrespective of subtype, in Uganda. J. Med. Virol. 86: 1796–1803, 2014. © 2014 Wiley Periodicals, Inc.